The Role of Thermodynamics in Model Reduction When Using Invariant Grids (Communications in Computational Physics, 2010)
In the present work, we develop in detail the process leading to reduction ofmodels in chemical kinetics when using the Method of Invariant Grids (MIG). To thisend, reduced models (invariant grids) are obtained by refining initial approximationsof slow invariant manifolds, and used for integrating smaller and less stiff systems ofequations capable to recover the detailed description with high accuracy. Moreover,we clarify the role played by thermodynamics in model reduction, and carry out acomparison between detailed and reduced solutions for a model hydrogen oxidationreaction.